2002
DOI: 10.1016/s1074-5521(02)00112-6
|View full text |Cite
|
Sign up to set email alerts
|

MgF3− as a Transition State Analog of Phosphoryl Transfer

Abstract: The formation of complexes between small G proteins and certain of their effectors can be facilitated by aluminum fluorides. Solution studies suggest that magnesium may be able to replace aluminum in such complexes. We have determined the crystal structure of RhoA.GDP bound to RhoGAP in the presence of Mg(2+) and F(-) but without Al(3+). The metallofluoride adopts a trigonal planar arrangement instead of the square planar structure of AlF(4)(-). We have confirmed that these crystals contain magnesium and not a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
121
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(126 citation statements)
references
References 27 publications
5
121
0
Order By: Relevance
“…x is not only a good mimic of the TS for phosphoryl transfer reactions (Graham et al 2002), but also that it can form under the crystallization conditions employed by Lahiri and co-workers. This was then later examined by detailed NMR studies that also provided insight in the molecular mechanism of fluoride inhibition by bPGM (Baxter et al 2006), as well as further (steady and pre-steady state) kinetic analysis of both the reactivity of bPGM and its inhibition by magnesium fluoride, which essentially ruled out the existence of a stable pentavalent phosphorane intermediate in the active site of bPGM (Golicnick et al 2009).…”
Section: B-phosphoglucomutase (Bpgm) : Metal Fluoride Ts Analogs As Pmentioning
confidence: 99%
“…x is not only a good mimic of the TS for phosphoryl transfer reactions (Graham et al 2002), but also that it can form under the crystallization conditions employed by Lahiri and co-workers. This was then later examined by detailed NMR studies that also provided insight in the molecular mechanism of fluoride inhibition by bPGM (Baxter et al 2006), as well as further (steady and pre-steady state) kinetic analysis of both the reactivity of bPGM and its inhibition by magnesium fluoride, which essentially ruled out the existence of a stable pentavalent phosphorane intermediate in the active site of bPGM (Golicnick et al 2009).…”
Section: B-phosphoglucomutase (Bpgm) : Metal Fluoride Ts Analogs As Pmentioning
confidence: 99%
“…12A). [23] The PDB now lists 16 entries for this ligand (PDB ligand: MGF) while a further 3 entries assigned as tbp AlF3 0 have been shown by 19 F NMR to be MgF3 -complexes (SI Table 8). [24] Magnesium is regularly 6-coordinate and gives octahedral complexes with oxygen ligands.…”
Section: Trifluoromagnesates Mgf3 -mentioning
confidence: 99%
“…Aluminum with fluoride bound to the enzymes was shown to be either AlF 3 or AlF 4 Ϫ compound (53,(55)(56)(57), and their formation also depends on pH in the incubation medium (56). The structural studies further revealed that both AlF 3 and AlF 4 Ϫ possess the planar (trigonal (AlF 3 ) and square (AlF 4 Ϫ )) geometry, in which two oxygen atoms coordinate to the aluminum at apical positions, for example, from the hydrolytic water molecule and the specific aspartate to produce the state superimposable (AlF 3 ) or analogous (AlF 4 Ϫ ) to the trigonal bipyramidal structure of the penta-coordinated phosphorus in the transition state of in-line associative acylphosphate hydrolysis mechanism, which was also predicted for the Ca 2ϩ -ATPase (58).…”
Section: Close Similarities and Differences Between E2p Analogues Andmentioning
confidence: 99%